(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The report examines the behaviour of a radionuclide released during an accident at a nuclear power plant. The analysis focuses exclusively on caesium to provide specific and detailed information about its characteristics and dispersion. Experiments were conducted under different atmospheric stability conditions to track changes in the plume's behaviour. The hypothetical model used in this analysis can be easily applied to assess radiation scenarios in similar events. This approach is instrumental in assisting first responders and guiding defensive actions. It also aids in establishing general operational guidelines and evaluating population exposure risks.